Ethnobotanical study on medicinal plants used by ethnic people of Gechi District, South West Oromia, Ethiopia - AMARE DESALEGN; MESERET C. EGIGU; JAGATHALA MAHALINGAM SASIKUMAR (Nusantara Bioscience, 2022)
Abstract. Desalegn A, Egigu MC, Sasikumar JM. 2022. Ethnobotanical study on medicinal plants used by ethnic people of Gechi District, South West Oromia, Ethiopia. Nusantara Bioscience 14: 104-116. This study recorded medicinal plants used by ethnic people of Gechi District, Buno Bedele zone of South West Oromia region, Ethiopia. Data were collected from 386 informants through semi-structured interviews, guided field observations, and focus group discussions. Descriptive statistics and quantitative ethnobotanical indices were used to analyze the data. Moreover, an independent t-test and one-way ANOVA were employed to investigate the effect of Sociodemographic traits on traditional medicinal knowledge. The study documented 70 medicinal plant species belonging to 61 genera and 36 families. Most plants (83.7%) were used to treat human ailments. Asteraceae (7 species) mainly represented the family. Most of the plants collected were shrubs (32.9 %), followed by herbs (25.7%). Leaves (42.3%) represented the highest part for remedy preparation. The dominant route of administration of remedies was oral (56%). Jaccard's similarity index (JI) showed a high degree of similarities (JI = 0.75-0.91) among three kebeles namely, Imboro, Koba, and Dike. The highest Informant consensus factor (ICF) value (0.73) was detected for the sensory organs category illnesses. Juniperus procera Hochst. Ex. Endl. was observed with the highest fidelity level (FL) index value (0.97) for the wound. The highest preference ranking (PR) was adjudged to be Ruta chalepensis L. for stomach ache. Syzygium guineense (Willd.) DC. was top-ranked as a multipurpose plant in direct matrix ranking (DR). It was observed that the Traditional Knowledge (TK) of medicinal plants was significantly (P<0.05) influenced by the gender, age, and educational level of the people. Therefore, our documentation of TK on medicinal plants possessed by the people of the studied area could help preserve their knowledge for extensive use.